Cheating Behaviors among Undergraduate College Students: Results from a Factorial Survey. Issue 2 (3rd April 2017) - Freiburger, Tina L.; Romain, Danielle M.; Randol, Blake M.; Marcum, Catherine D.
Abstract : Using a factorial survey administered to college students at two Universities, this study examines students' tendencies to engage in academic misconduct. The relation of strain, self-control, and deterrence theories to likelihood of cheating are further explored. The results suggest that increasing the severity of the punishment for cheating does not deter academic misconduct; however, several variables indicating an increased certainty of being caught did decrease the likelihood of cheating behaviors. Only the strain variables that indicated a student had an ill family member or that the student found the course difficult significantly increased academic misconduct. Although self-control did not have a direct effect on cheating it indirectly affected cheating behaviors through students' perceptions of getting caught and their perception of wrongfulness of the cheating behavior. Policy and future research implications of the findings are further discussed.